Molecular Detection of Some Capsulargenes of Klebsiella pneumoniaeIsolated from Clinical Samples - Amina A. Raheem; Ghaidaa J. Mohammed (Al-Qadisiyah Journal of Pure Science, 2021)
Klebsiella pneumoniae is an opportunistic pathogen that has been implicated as one of commonest cause of hospital and community acquired infections.The capsule of Klebsiella pneumoniae is an important virulence factor, involved in pathogenic mechanisms.So, this study aimed to isolateKlebsiella pneumoniae from different clinical samples from patients in Al-Diwaniyah teaching hospital and determine some virulence factors (capsulegenes)that used for serotyping of isolates. The study extended fromAugust to November 2020.A total of 31 isolates from 80 different clinical samples identified as Klebsiella pneumoniae by traditional biochemical tests ,Vitek system and 16SrRNA gene.The existenceof three genes from7tested capsulargenes wasdetectedby Polymerase chain reaction.The commonness serotype were k2,k54,k57 where K2 detected in 4 (12.9 %), K54 in 12 (38.7 %),k57 in 4 (12.9).But, the other capsular polysaccaride genes k1,k3,k5,k20not detectedin all isolates of this study.